2016
DOI: 10.4067/s0718-221x2016005000036
|View full text |Cite
|
Sign up to set email alerts
|

Sorption behavior of four tropical woods using a dynamic vapor sorption standard analysis system

Abstract: Sorption behavior of four tropical woods coming from Cameroon is studied using a Dynamic Vapor Sorption-Intrinsic apparatus. Sorption isotherms at 20°C and 40°C of Triplochiton scleroxylon (obeche), Entandrophragma cylindricum (sapele), Sterculia rhinopetala (lotofa) and Terminalia superba (frake also called limba) are compared to those in the literature with methods using saturated salts for lotofa and frake with satisfactory results. Experimental values are fitted using two sorption isotherm models.Sorption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…The standard deviation associated with the moisture content measurement varied between 0,09 and 0,42%. Many models such as the Hailwood-Horrobin and GAB (Guggenheim-Andersen-de Boer) isotherms have been developed and utilised to describe the sorption behaviour of wood (Simpson 1973, Avramidis 1989, Sargent et al 2010, Simo-Tagne et al 2016. In this study, a 4 th order polynomial was found to have the best fit to the experimental data and is used to express the moisture content as a function of relative humidity at a temperature of 20°C (Equation 3).…”
Section: Materials Characterisation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The standard deviation associated with the moisture content measurement varied between 0,09 and 0,42%. Many models such as the Hailwood-Horrobin and GAB (Guggenheim-Andersen-de Boer) isotherms have been developed and utilised to describe the sorption behaviour of wood (Simpson 1973, Avramidis 1989, Sargent et al 2010, Simo-Tagne et al 2016. In this study, a 4 th order polynomial was found to have the best fit to the experimental data and is used to express the moisture content as a function of relative humidity at a temperature of 20°C (Equation 3).…”
Section: Materials Characterisation Resultsmentioning
confidence: 99%
“…This is primarily due to the similar cell wall structure within all species (Wadsö 1993). Many models have been created to determine the average equilibrium moisture content of timber as a function of the relative humidity and temperature (Hailwood and Horrobin 1946, Simpson 1973, Avramidis 1989, Sargent et al 2010, Simo-Tagne et al 2016, however, these models do not consider the moisture content hysteresis of timber during adsorption and desorption. Merakeb et al (2009) and Patera et al (2015) have investigated and modelled the influence of the hysteresis effect on moisture transport in timber.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, several authors conducted investigations concerning the mass transfer properties of wood (11) K D = K 0 exp(K 0w w), [25,26]. Concerning central Africa tropical woods, some results on species like sapelli (Entandrophragma cylindricum) and sipo (Entandrophragma utile) are available [27][28][29]. Such timber species present similar technological properties with Bete [30].…”
Section: Diffusion and Exchange Coefficientsmentioning
confidence: 99%
“…Otherwise, the sorption isotherms have an importance in the modeling of the drying to wetting process, determining the storage properties, and shelf‐life stability of materials 24‐26 . However, few works in the literature dealing with characterizing the properties of building materials have been performed and particularly on modeling the sorption isotherms of building materials.…”
Section: Introductionmentioning
confidence: 99%